2019
DOI: 10.3928/02793695-20190626-01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mindfulness Activity on Nursing Service Staff Perceptions of Caring Behaviors in the Workplace

Abstract: Research on caring in nurse-to-nurse relationships is not extensive, but studies have shown that health care workers can experience incivility in the workplace and unhealthy relationships can increase stress and influence nurse retention. The current study examined nurse perceptions of caring in the workplace and the effect of a mindfulness activity. A mixed method design was used, and data were collected on 164 nursing staff members after a 1-minute mindfulness activity. Pre- and post-survey growth in caring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Religious activities play a vital role in the patients' healing process and reduce mental disorders and cardiovascular problems (24,25). Mindfulness basically shows an increase in the perception of individuals who can focus their activities so that individuals can focus back on their environment (26). The results showed that mindfulness as mind therapies is carried out with a spiritual approach.…”
Section: Mind Terapiesmentioning
confidence: 99%
“…Religious activities play a vital role in the patients' healing process and reduce mental disorders and cardiovascular problems (24,25). Mindfulness basically shows an increase in the perception of individuals who can focus their activities so that individuals can focus back on their environment (26). The results showed that mindfulness as mind therapies is carried out with a spiritual approach.…”
Section: Mind Terapiesmentioning
confidence: 99%
“…Other scholars have used asynchronic learning models to decrease incivility [20]. For the most part, these interventions have been conducted in healthcare organizations and in academia [18,20,21,38,39], but not in other public service contexts. Moreover, although all these interventions were based on learning, none were founded in a holistic view; that is, none was aimed at creating sustainable change based on lifelong learning as a way of increasing the ability of individuals to respond to change and to flourish.…”
Section: Mitigation Of Mistreatmentmentioning
confidence: 99%
“…This theory highlights the sense of honor, help, trust, and building caring relationships. Subsequently, the balance between teaching and learning practices is considered the main element to fulfill the individual's needs and creation of caring, and healing environment addressing the fulfillment of overall care (Watson, 1997;King et al, 2019), by understanding the patient as a person and addressing their health care needs. As for the caregivers and entrepreneurs, their services to the elderly may enhance their sense of honor and create a strong bond and trust between them and the elderly, and with the elderly family members, who are responsible for their parents' overall well-being and cost provision.…”
Section: Underpinning Theoriesmentioning
confidence: 99%